Pengaruh Keterbatasan Sistem Informasi dan Otoritas Pengambilan Keputusan terhadap Akuntabilitas Kinerja Instansi Pemerintah Daerah - Sapulette, Shella Gilby; Limba, Franco Benony (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to empirically analyze the influence of information system limitations and decision making authority on performance accountability of local government agencies by using quantitative approach and is tested using SPSS 24. This research was conducted in 10 districts/ cities in Maluku province with the sample amounted to 96 employees. Sampling technique used purposive sampling method. The results of this study show that the information system limitations do not affect the performance accountability of local government, while the decision making authority affect the performance accountability of local government at the 5% significance level.